Issues of language contacts and oralitures in ogresse names in Babors Kabylia - (:unkn) unknown (My University, 2025)
The Babor Kabylia is a coastal mountain region in northeastern Algeria. Three Amazigh languages are spoken here: Tabǧawit (or Eastern Kabyle), Taɛemmuct (or Amoucha Chaouia) and Tasaḥlit. One of the major figures of the Amazigh and North African tale is the ogress. She is described as a female creature, living alone or in a family, isolated from men and able to feed on them. Based on a corpus of tales collected from women from different Babor confederations since 2017, I have compiled the names and main characteristics attributed to ogres and ogresses, with the aim of questioning the consequences of language contact, but also that of cultures, through Amazigh oral literature, with the Amazigh languages of the Babors as a case in point. This work provides a better understanding of the relationships between the ancient (Romans and Latin-speaking Amazighs), medieval and contemporary (Arabs and Derjaphon Amazighs) worlds, and the Amazigh-speaking populations of North Africa.
Keywords: African Research